MANAJEMEN ASET TERHADAP PEMBENTUKAN PROFITABILITAS DAN NILAI PERUSAHAAN MANUFAKTUR - Wahyu Hari Prihantono; Rudiyanto Rudiyanto (The Asia Pacific Journal Of Management Studies, 2017)
This study aims to prove the three hypotheses proposed, namely: (1) whether the effectiveness affects profitabilias ?, (2) does the profitability affect the formation of corporate value ?, and (3) whether the efficiency affects the value of the company ?. The study was conducted by using secondary data taken from summary financial reports of multinational companies from various sectors. The sample in this study used 24 companies consisting of 240 data. To summarize the results of this study using Partial Least Square (PLS) analysis used in the discussion. Based on the calculation, this study concludes that the efficiency of the company through asset management affect the formation of profitability, as well as the value of the company. But profitability is not able to prove significantly.